PEMETAAN KUALITAS PERAIRAN PAYAU YANG POTENSIAL DI TAMBAK KUALA LANGSA - Agustinus Sinaga (Fakultas Pertanian Universitas Samudra, 2021)
This study was conducted to determine the potential quality of waters in the pond in Kuala Langsa village and provide an output in the form of a map of the suitability of water quality in aquaculture activities in Kuala Langsa. The method used was a survey method by collecting water quality data on physical and chemical parameters that were directly in the ponds of Kuala Langsa Village in December in two periods. From the research results, it is obtained that the potential quality of brackish waters in the Kuala Langsa Village pond is in zone I and III with the following parameter values; temperature 30.08-30.68 oC, salinity 30.08-30.92 ppt, dissolved oxygen 3.12-4.79 mg / l, pH 6.75-6.83, TSS 7 mg / l, ammonia 0 , 4 mg / l, Nitrate 0.11-0.33 mg / l, Nitrite 0.01-0.03 mg / l.